Syndromes of production in intercropping impact yield gains - Li, Chunjie; Hoffland, Ellis; Kuyper, Thomas W.; Yu, Yang; Zhang, Chaochun; Li, Haigang; Zhang, Fusuo; van der Werf, Wopke (Nature plants, 2020)
Intercropping, the simultaneous production of multiple crops on the same field, provides opportunities for the sustainable intensification of agriculture if it can provide a greater yield per unit land and fertilizer than sole crops. The worldwide absolute yield gain of intercropping as compared with sole crops has not been analysed. We therefore performed a global meta-analysis to quantify the effect of intercropping on the yield gain, exploring the effects of crop species combinations, temporal and spatial arrangements, and fertilizer input. We found that the absolute yield gains, compared with monocultures, were the greatest for mixtures of maize with short-grain cereals or legumes that had substantial temporal niche differentiation from maize, when grown with high nutrient inputs, and using multirow strips of each species. This approach, commonly practised in China, provided yield gains that were (in an absolute sense) about four times as large as those in another, low-input intercropping strategy, commonly practised outside China. The alternative intercropping strategy consisted of growing mixtures of short-stature crop species, often as full mixtures, with the same growing period and with low to moderate nutrient inputs. Both the low- and high-yield intercropping strategies saved 16–29% of the land and 19–36% of the fertilizer compared with monocultures grown under the same management as the intercrop. The two syndromes of production in intercropping uncovered by this meta-analysis show that intercropping offers opportunities for the sustainable intensification of both high- and low-input agriculture. Intercropping can provide for agricultural intensification within a sustainable footprint. This study of Chinese methods finds yields four times greater than intercropping outside China with less land and fertilizer use.